Critical terms for the study of (colonial) art from Quito - Fernández-Salvador, Carmen (2025)
In recent years, various scholars have emphasized the connection between the emergence of the disciplines of history and art history, and the writing and invention of national narratives. This essay analyzes the persistent use or neglect of critical terms in the texts of key authors, such as Juan León Mera and José Gabriel Navarro, who during the second half of the nineteenth century and the first decades of the twentieth century were concerned with shaping a history of art in Ecuador, laying the foundations for future studies. This discussion allows us to question the writing of art history in Latin America, and particularly in Ecuador, and the relationship between this discipline and a homogenizing and excluding political project. Keywords: historiography, colonial art, artistic school, canon, race, Juan León Mera, José Gabriel Navarro